(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The aim of this study is to investigate the preferences of Ukrainian students in the way of learning in lectures. The paper provides an answer to the following didactic and research question: "How to teach?" in the context of the reform of Ukrainian Higher Education. In paper, we see students as clients because their preferences are clients’ requirements. Statistically proven that Ukrainian students do not prefer the auditory way of learning in lectures. The result is statistically significant (95.0%). The result of the study may be useful at the input stage of the reform of Ukrainian Higher Education, including for the formation of training programs for teachers.